How do you solve the system -5 = -64a + 16b - 4c + d5=64a+16b4c+d, -4 = -27a + 9b - 3c + d4=27a+9b3c+d, -3 = -8a + 4b - 2c + d3=8a+4b2c+d, 4 = -a + b - c + d4=a+bc+d?

2 Answers
Mar 5, 2017

{ (a=1), (b=9), (c=27), (d=23) :}

Explanation:

Given:

{ (-5 = -64a+16b-4c+d), (-4 = -27a+9b-3c+d), (-3 = -8a+4b-2c+d), (4 = -a+b-c+d) :}

Consider the function:

f(x) = ax^3+bx^2+cx+d

Note that the given system of equations is equivalent to:

{ (f(-4) = -5), (f(-3) = -4), (f(-2) = -3), (f(-1) = 4) :}

Since the sampling points are at equal intervals of size 1, we can conveniently find a formula for a cubic function satisfying this system by examining differences...

Start with the original values:

color(blue)(-5), -4, -3, 4

Write down the sequence of differences between successive terms:

color(blue)(1), 1, 7

Write down the sequence of differences between successive terms:

color(blue)(0), 6

Write down the sequence of differences between successive terms:

color(blue)(6)

Then we can write down a formula for f(x) using the initial term of each of these sequences (see footnote):

f(x) = color(blue)(-5)/(0!)+color(blue)(1)/(1!)(x+4)+color(blue)(0)/(2!)(x+4)(x+3)+color(blue)(6)/(3!)(x+4)(x+3)(x+2)

color(white)(f(x)) = -5+x+4+x^3+9x^2+26x+24

color(white)(f(x)) = x^3+9x^2+27x+23

So:

{ (a=1), (b=9), (c=27), (d=23) :}

color(white)()
Footnote

Note that:

color(purple)(1/(0!))_(color(white)(1/1)) is a constant function taking the value 1 when x = -4

color(purple)(1/(1!)(x+4))_(color(white)(1/1)) is a linear function taking the value 0 when x = -4 and 1 when x = -3

color(purple)(1/(2!)(x+4)(x+3))_(color(white)(1/1)) is a quadratic function taking the value 0 when x = -4 or x = -3 and the value 1 when x = -2

color(purple)(1/(3!)(x+4)(x+3)(x+2))_(color(white)(1/1)) is a cubic function taking the value 0 when x = -4, x = -3 or x = -2 and the value 1 when x = -1

So as we add suitable multiples of these functions in turn, we get a sequence of polynomials of increasing degree that match each of the sample points in turn. The suitable multiples are the differences we found.

Mar 5, 2017

{ (a=1), (b=9), (c=27), (d=23) :}

Explanation:

Given:

{ (-5 = -64a+16b-4c+d), (-4 = -27a+9b-3c+d), (-3 = -8a+4b-2c+d), (4 = -a+b-c+d) :}

Write in matrix form:

((-64, 16, -4, 1, -5),(-27, 9, -3, 1, -4),(-8, 4, -2, 1, -3),(-1, 1, -1, 1, 4))

Perform some row operations to make the left hand side into a 4xx4 identity matrix. These may not be optimal, but this is a sequence I found...

Subtract 3xx"row"2 from "row"1 to get:

((17, -11, 5, -2, 7),(-27, 9, -3, 1, -4),(-8, 4, -2, 1, -3),(-1, 1, -1, 1, 4))

Add 2xx"row"1 to "row"2 to get:

((17, -11, 5, -2, 7),(7, -13, 7, -3, 10),(-8, 4, -2, 1, -3),(-1, 1, -1, 1, 4))

Add 2xx"row"3 to "row"1 to get:

((1, -3, 1, 0, 1),(7, -13, 7, -3, 10),(-8, 4, -2, 1, -3),(-1, 1, -1, 1, 4))

Add "row"1 + "row"3 to "row"2 to get:

((1, -3, 1, 0, 1),(0, -12, 6, -2, 8),(-8, 4, -2, 1, -3),(-1, 1, -1, 1, 4))

Add 8xx"row"1 to "row"3 to get:

((1, -3, 1, 0, 1),(0, -12, 6, -2, 8),(0, -20, 6, 1, 5),(-1, 1, -1, 1, 4))

Add "row"1 to "row"4 to get:

((1, -3, 1, 0, 1),(0, -12, 6, -2, 8),(0, -20, 6, 1, 5),(0, -2, 0, 1, 5))

Subtract "row"2 from "row"3 to get:

((1, -3, 1, 0, 1),(0, -12, 6, -2, 8),(0, -8, 0, 3, -3),(0, -2, 0, 1, 5))

Subtract "row"3+"row"4 from "row"2 to get:

((1, -3, 1, 0, 1),(0, -2, 6, -6, 6),(0, -8, 0, 3, -3),(0, -2, 0, 1, 5))

Divide "row"2 by -2 to get:

((1, -3, 1, 0, 1),(0, 1, -3, 3, -3),(0, -8, 0, 3, -3),(0, -2, 0, 1, 5))

Subtract 4xx"row"4 from "row"3 to get:

((1, -3, 1, 0, 1),(0, 1, -3, 3, -3),(0, 0, 0, -1, -23),(0, -2, 0, 1, 5))

Add "row"3 to "row"4 to get:

((1, -3, 1, 0, 1),(0, 1, -3, 3, -3),(0, 0, 0, -1, -23),(0, -2, 0, 0, -18))

Multiply "row"3 by -1 and divide "row"4 by -2 to get:

((1, -3, 1, 0, 1),(0, 1, -3, 3, -3),(0, 0, 0, 1, 23),(0, 1, 0, 0, 9))

Permute rows 2, 3 and 4 to get:

((1, -3, 1, 0, 1),(0, 1, 0, 0, 9),(0, 1, -3, 3, -3),(0, 0, 0, 1, 23))

Subtract "row"2 from "row"3 to get:

((1, -3, 1, 0, 1),(0, 1, 0, 0, 9),(0, 0, -3, 3, -12),(0, 0, 0, 1, 23))

Divide "row"3 by -3 to get:

((1, -3, 1, 0, 1),(0, 1, 0, 0, 9),(0, 0, 1, -1, 4),(0, 0, 0, 1, 23))

Add "row"4 to "row"3 to get:

((1, -3, 1, 0, 1),(0, 1, 0, 0, 9),(0, 0, 1, 0, 27),(0, 0, 0, 1, 23))

Add 3xx"row"2 - "row"3 to "row"1 to get:

((1, 0, 0, 0, 1),(0, 1, 0, 0, 9),(0, 0, 1, 0, 27),(0, 0, 0, 1, 23))

We can now read off a, b, c, d from the last column as:

{ (a=1), (b=9), (c=27), (d=23) :}